2016
DOI: 10.4103/0300-1652.188341
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and knowledge of National School Health Policy and School Health Programme among public secondary school teachers in Ibadan metropolis

Abstract: Background:The awareness, knowledge, and involvement of teachers in the implementation of School Health Programme (SHP) in secondary schools are essential in ensuring the effectiveness and overall success of the School Health Policy. This study assessed the awareness and knowledge of teachers on SHP in Ibadan metropolis.Methods:A descriptive cross-sectional study was carried out using a two-stage sampling technique to select 426 secondary school teachers across all the five Urban Local Government Areas (LGAs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 21 publications
3
18
1
Order By: Relevance
“…The age distribution of the teachers showed that almost half of them were between the ages of 40-49 years and the mean age was 42.64±7.779 years. This distribution is similar to the population in a study conducted by Obembe, Osungbade & Ademokun (2016) and Annadurai (2018). In accordance with the civil service retirement age, none of the teachers was above 60 years of age.…”
Section: Discussionsupporting
confidence: 87%
“…The age distribution of the teachers showed that almost half of them were between the ages of 40-49 years and the mean age was 42.64±7.779 years. This distribution is similar to the population in a study conducted by Obembe, Osungbade & Ademokun (2016) and Annadurai (2018). In accordance with the civil service retirement age, none of the teachers was above 60 years of age.…”
Section: Discussionsupporting
confidence: 87%
“…In the current study, the findings indicate that 19.6% of high school teachers were those with a high level of knowledge regarding HPS program. It was lower than the findings of previous studies done in Myanmar with 62.9% of a high level of knowledge [ 26 ], Nigeria with 49.8% and 55.9% of good knowledge [ 51 , 52 ], India with 40% of moderately adequate knowledge [ 47 ] and 22% of moderately adequate knowledge [ 48 ]. Conversely, it was higher than the findings of the other studies done in Nigeria with 8% of a good level of knowledge [ 43 ], 15.4% with adequate knowledge [ 53 ], and 16.3% with a good level of knowledge [ 41 ].…”
Section: Discussioncontrasting
confidence: 69%
“…2,12 However, this finding is in discordance with the reports from studies that were conducted in Sagamu and Ibadan South-western Nigeria where most of the teachers were at least first degree holders. 11,25,26 A plausible explanation for this variation could be due to the fact that this study was among primary school teachers only as opposed to the studies conducted in Sagamu and Ibadan where they interviewed both the primary and secondary school teachers. Most of the respondents have been in service for less than 10 years.…”
Section: Data Collection and Analysismentioning
confidence: 94%